Role of GCR positive and negative particles in charging the LISA-PF test masses in 2015. (April 2015) - Grimani, C; Fabi, M; Lobo, A J; Mateos, I; Telloni, D
Abstract: The LISA Pathfinder (LISA-PF) mission launch is scheduled during the second half of 2015. Galactic and solar ions with energies larger than 100 MeV/n and electrons above 10 MeV penetrate the spacecraft material and charge the gold-platinum test masses. This charging process generates spurious forces that, in some cases, may mimic the effects of genuine gravitational wave signals. A study of the test-mass charging due to galactic cosmic rays (GCRs) down to 1% in composition is reported here. The reliability of the results of this work is mainly limited by our capability to predict the energy spectra of GCRs in 2015. To this purpose, our model is applied to the expected PAMELA experiment proton data for the period January- March 2014 characterized by a positive polarity period and a level of solar modulation similar to those expected at the time of LISA-PF. The PAMELA observations will be available in the next few months. The comparison between our projections and measurements will provide valuable clues on the test-mass charging estimate uncertainty.